2024
DOI: 10.3390/vetsci11010048
|View full text |Cite
|
Sign up to set email alerts
|

Veterinarian—Chasing A Dream Job? A Comparative Survey on Wellbeing and Stress Levels among European Veterinarians between 2018 and 2023

Wiebke Jansen,
Lizzie Lockett,
Tricia Colville
et al.

Abstract: Whilst recognizing the abundantly positive aspects within the different domains of the veterinary profession, the challenging socio-economic and cultural working climate has been identified as a source of veterinary mental wellbeing issues. This mixed methods study provides an overview of the mental state of veterinarians across Europe via two cross-sectional surveys in 2018/2019 (n = 14,559 veterinarians) and in 2022/2023 (n = 12,393 veterinarians). Mental wellbeing was assessed using 3 indicators: self-repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…The proportions of sickness absence and early retirement due to mental health issues have risen across Europe over the past few decades 32 . A recent study, conducted in 2022/2023 on European veterinarians 33 , revealed that 23% of veterinarians reported more than 2 weeks off-work due to burnout, exhaustion, compassion fatigue, or depression within the past 3 years. These percentages varied greatly among countries, with Luxembourg and Hungary reporting lower rates, while Latvia and North Macedonia reported higher rates.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of sickness absence and early retirement due to mental health issues have risen across Europe over the past few decades 32 . A recent study, conducted in 2022/2023 on European veterinarians 33 , revealed that 23% of veterinarians reported more than 2 weeks off-work due to burnout, exhaustion, compassion fatigue, or depression within the past 3 years. These percentages varied greatly among countries, with Luxembourg and Hungary reporting lower rates, while Latvia and North Macedonia reported higher rates.…”
Section: Discussionmentioning
confidence: 99%